TRANSFORMASI LAYANAN SAMSAT: MENAKAR DAMPAK KUALITAS PELAYANAN TERHADAP KEPUASAN WAJIB PAJAK KENDARAAN BERMOTOR DI TASIKMALAYA - Ramdani, Ramdani Al Falah; Zulfikar Bintang Satrio, Muhamad; Setia Rachmanda, Yudi; Agustiana, Aldy; Riswandi, Dede (LP2M Universitas Perjuangan Tasikmalaya, 2025)
The purpose of this research is to find out and analyze the Quality of Service Against Satisfaction of Taxpayers in Payment of Motorized Vehicle Taxes in Samsat, Tasikmalaya Regency. The research method used is descriptive method with quantitative approach. Data collection techniques using interviews, questionnaires, and literature studies. The sampling technique by determining the sample to be taken using the formula proposed by Sugiyono. Based on the results of the study, it is known that the Quality of Service Against Satisfaction of Taxpayers in Paying Taxes on Motorbikes in Samsat Sub-District of Tasikmalaya prefers to agree to the satisfaction of taxpayers. Quality of Service Against Satisfaction Taxpayers are tested using the t test results of a significant correlation and based on F test Quality of Service also has a significant effect on Satisfaction of Taxpayers in Payment of Motorized Taxes on Samsat Tasikmalaya Regency